The one and the multiple. The arrival of modernity in the Andes: a reading of César Vallejo’s Fabla salvaje (1923) - Mudarra Montoya, Américo (2023)
This research postulates that Fabla salvaje (1923), a novel by César Vallejo, represents an epistemic violence that marks the full entry of modern subjectivity into the Andean world. The novel proposes, then, how modernity, through the dynamics of isolation and denial of dialogue, penetrates in the calm of the Andean world and breaks the prerogatives of the family or animal horizontality by rendering them strange and useless. This phenomenon is represented in Balta Espinar, the protagonist of the novel, as well as in his relations with his wife and with the nature that surrounds him. In order to demonstrate this hypothesis, the contributions of the French philosophers Gilles Deleuze and Félix Guattari will be used. The aim is to show how the novel narrates the distancing from the multiplicity of the surrounding life and the concentration on the unity of the subject. The transition from the multiple to the unique leads, finally, to the annihilation of the protagonist.